Comparison of Abbott real time SARS-COV-2 assay and Liferiver Novel Coronavirus Real Time Multiplex kit for the RT-PCR based detection of SARS-COV-2 from nasopharyngeal swabs - Jelena Stojčević-Maletić; Iva Barjaktarović; Mirjana Đerić; Velibor Čabarkapa; Vladimir Petrović; Aleksandra Patić; Slobodanka Bogdanović-Vasić (Acta Clinica Croatica)
The objective of this study was to compare performance of two authorized tests, the Abbott Real Time SARS–CoV-2 (ACOV) assay (Abbott Molecular Inc., North Chicago, IL, USA) and Liferiver Novel Coronavirus Real Time Multiplex RT-PCR (Liferiver 2019-nCoV) kit (BioVendor Group, Brno, Czech Republic), and to determine whether the selection of targeted genes has an impact on test specificity. We included 105 nasopharyngeal swabs from adult individuals with symptoms or suspected of coronavirus disease 2019 (COVID-19), aged from 26 to 91 years, previously tested by the ACOV and subsequently tested by the Liferiver 2019-nCoV. In this comparative analysis, we found that the ACOV assay detected more cases of COVID-19 infection than the Liferiver 2019- nCoV assay. The Liferiver 2019-nCoV kit showed a high level of agreement with the ACOV assay. The positive percent agreement was 88.89% (95% confidence intervals (95% CI): 77.42%-100.0%), and the kappa coefficient (kappa) was 0.901 (95% CI: 0.817-0.985). The negative percent agreement was 94.12% (95% CI: 89.74%-98.50%), while 4.76% of SARS-CoV-2 cases were false-negative using the Liferiver test. However, due to the possible false-negative results using the Liferiver 2019-nCOV test, we recommend complete testing with the ACOV assay.